Comparison of user‐friendliness and treatment cost of Loceryl® vs. Ciclopoli® – a patient's perspective. Issue 10 (7th September 2015) - Schaller, M.; Braunsdorf, C.; Mailänder‐Sanchez, D.; Jäckel, A.; Müller, J.; Borelli, C.
Summary: Topical monotherapy is a valid therapeutic approach in onychomycosis. Due to its lengthy course and its non‐reimbursed product status, cost and compliance are important issues and non‐pharmacological properties such as over‐the‐counter price and ease of use should be considered when deciding which product to recommend. We investigated surrogate parameters for patient‐friendliness and treatment cost in Germany in a questionnaire‐based prospective, comparative, intra‐individual, open‐label trial of the two common topical antifungal nail lacquers Loceryl ® (amorolfine 5%) and Ciclopoli ® (ciclopirox 8%) in eight patients with clinically diagnosed onychomycosis. The 2.5 ml bottle of Loceryl ® covered a treatment period of 308 days, resulting in treatment costs of €0.10 per day in comparison to the 3.3 ml bottle of Ciclopoli ®, covering 127 days at €0.21 per day, given once‐daily application for Ciclopoli ® and once‐weekly application for Loceryl ® in accordance with regulatory approval. Six out of eight patients favoured the Loceryl ® treatment regimen. Furthermore, four out of eight patients found Loceryl ® easier to apply, whereas three preferred Ciclopoli ® . In total, seven out of eight stated a clear preference for Loceryl ® over Ciclopoli ® . Loceryl ® therapy is less expensive and less time‐consuming. The therapeutic period that can be covered is longer and more patients stated a clear preference for Loceryl ® in comparison to Ciclopoli ® . The differences are statistically significant, underlining probable clinical relevance.